Customer perceptions of technology-based banking service quality and its relationship to customer satisfaction and loyalty - Redda, Ephrem Habtemichael (Vaal University of Technology, 2012)
The rapid advancement in technology-based systems, especially those related to the Internet, has led to fundamental changes in how banks interact with customers. This study provides a framework for understanding customer perceptions of the quality of technology-based banking service and the relationship of this service to customer satisfaction and loyalty. The conceptual framework of this study was based on extensive study of relevant literature and examination of previously developed measuring instruments of service quality in general and e-service quality and online banking in particular. A modified and fully structured questionnaire was developed to suit the South African setting. Given the nature of this study, a quantitative research approach was applied. Customers from Southern Gauteng, South Africa, who made use of online banking facilities from commercial banks, constituted the population for the study. The sampling procedure (snowball sampling technique) resulted in a sample of 180 online banking consumers. Seven factors were extracted as dimensions that influence customer perception of online banking service quality, using a factor analysis and rotated factor loadings procedure. These were: factor 1 (assurance, trust and appeal), factor 2 (responsiveness), factor 3 (ease of use), factor 4 (accessibility), factor 5 (fulfilment), factor 6 (speed and accuracy) and factor 7 (contact). The percentage of variance explained, eigenvalues and scree plot were used in the process of determining the number of factors to extract for the study. With mean values above four on a scale of one (minimum) to five (maximum), all the factors were found to be critical for improvement of online banking service quality. The overall level of customer satisfaction with online banking service quality was very high, with an overall mean score of 4.22. A mean score of 4.10 for customer loyalty predicts that respondents are likely to commit to patronising their current bank in the foreseeable future. Thus, the overall customer satisfaction and loyalty levels were skewed to the right, suggesting that respondents were generally satisfied with the quality of service rendered by the banks. These high levels of customer satisfaction and loyalty should encourage the marketing practitioners of the banks to enhance online banking service quality and ensure its improvement in order to achieve delighted customers. The relationship among the constructs of online banking service quality, customer satisfaction and loyalty was established by using correlations and regression analysis. From the findings, it was established that there is evidence that the seven factors positively influence customer satisfaction and loyalty. The results also highlighted a strong positive influence of customer satisfaction on customer loyalty. Customer satisfaction has become a ‘must achieve’ objective for any bank that wishes to remain profitable and relevant in this competitive business environment. Acquiring loyal customers who will patronise and associate themselves with the bank is of particular importance for the potential market share growth and success of any bank. The relationship among the constructs of online banking service quality dimensions, customer satisfaction and loyalty focus must, however, be based on the individual building blocks of service quality, i.e. the factors (service attributes) that influence online banking service quality. Periodic measurement of the levels of online banking service quality should become an integral part of any bank`s effort and strategy in improving service quality levels. The study, which focused on users of Internet banking in South Africa, was not organisation/bank-specific. For more practical purposes, future endeavours could be focused on organisation/bank-specific studies. It must be emphasised that more research is needed before any final conclusions can be reached on the dimensionality and validity of online banking service quality.
M. Tech. (Department of Marketing and Sport Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Service quality; e-service quality; Online banking; Internet banking; Customer perceptions; Satisfaction; Post-purchase intentions; Loyalty; Dissertations, Academic -- South Africa; Banks and banking -- South Africa; Banks and banking -- Customer services; Internet banking